Addition of Germicidal UV-C Radiation Equipment in the Sterilization Process to Extend the Shelf Life of Cow's Milk - Wulansarie, Ria; Rusiyanto, Rusiyanto; Dino Alfian, Rangga; Diyah Ayu Utami, Kiki; Rahmah, Ladunia; Izza Arinanda, Miftakhul; Dyah Pita Rengga, Wara (Rekayasa, 2024)
Cow's milk provides essential human nutrients, including calcium, protein, and minerals. However, it is highly susceptible to bacterial contamination, which leads to rapid spoilage. Pasteurization is the most common method to process cow's milk, effectively reducing microbial levels. However, some heat-resistant bacteria can survive the pasteurization process, limiting its effectiveness in ensuring long-term milk safety. This study investigates the use of chemical engineering technology by combining pasteurization and UV-C radiation methods, either sequentially or simultaneously, to improve the effectiveness of milk sterilization. The use of combined techniques aims to leverage the strengths of both processes, achieving superior microbial reduction and extending milk shelf life. Different operating temperatures and radiation durations were tested to identify optimal processing conditions. The findings revealed that this combined approach achieved a significant bacterial reduction of 99.95%, decreasing the microbial count from an initial 1.9 × 10⁶ cfu/mL to 7.0 × 10² cfu/mL. Moreover, the shelf life of the milk was extended to five months, demonstrating the effectiveness of the hybrid method. The study also monitored the milk's acidity (pH) throughout the process, which remained within optimal conditions of 6.5 to 6.8. This indicates that the combined treatment does not compromise milk quality. Integrating pasteurization with germicidal UV-C radiation offers a promising alternative for milk sterilization, improving microbial control and significantly increasing the shelf life of cow's milk. The results suggest that this dual-method approach could be a valuable advancement in dairy processing, enhancing both safety and efficiency in the production and preservation of milk.